Pharmaceutical composition containing pimitinib

By using compound 1 for granularity and adding crystal cellulose, the problem of disintegration and biological utilization in pharmaceutical compounds in pharmaceutical compounds is solved, and excellent disintegration and biological utilization are achieved, and the problem of compression is avoided.

CN119365195APending Publication Date: 2025-01-24TAIHO PHARMA CO LTD

Patent Information

Application Number
CN202380046118.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-06-09
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Compound 1 has problems with disintegration and bioavailability in pharmaceutical compositions for oral administration, especially in tableting problems such as adhesions and other tableting problems are prone to occur under direct tableting method.

Method used

By pressing the compound 1 or the acceptable salt in its pharmacy, and adding a specified crystalline cellulose to the granular to increase the crushing of the pharmaceutical composition, the collapse and biological utilization of the pharmaceutical composition are improved.

Benefits of technology

Achieve the excellent disintegration and biological utilization of compound 1 pharmaceutical composition, avoid the pressure of adhesion, etc., and ensure the stability and effectiveness of the drug.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119365195A_ABST
    Figure CN119365195A_ABST
Patent Text Reader

Abstract

The present invention provides a pharmaceutical composition containing Compound 1, which has excellent disintegrability and bioavailability. The present invention relates to a pharmaceutical composition comprising: a granulated material containing 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo [3, 4-b] pyridin-1-yl} benzamide or a pharmaceutically acceptable salt thereof, and a crystalline cellulose, the granulated material being characterized in that: the granulated material contains a compound represented by general formula (1); the pharmaceutical composition has a disintegration time within 360 seconds in a coated tablet state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a pharmaceutical composition, particularly a pharmaceutical composition for oral administration, containing 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide (hereinafter also referred to as "Compound 1") or a pharmaceutically acceptable salt thereof and crystalline cellulose, and a method for producing the same. Background Art

[0002] A group of proteins called molecular chaperones play a role in forming, promoting or maintaining the functional structure of other proteins, promoting correct association, inhibiting unnecessary aggregation, protecting against degradation, promoting secretion, etc. HSP90 is a molecular chaperone that exists in large quantities, accounting for about 1-2% of all soluble proteins in cells, but unlike other chaperone proteins, it is not essential for the biosynthesis of most polypeptides (Non-patent Document 1). As the main client proteins that interact with HSP90 and control its structure formation and stability, signal transduction-related factors (such as ERBB1 / EGFR, ERBB2 / HER2, MET, IGF1R, KDR / VEGFR, FLT3, ZAP70, KIT, CHUK / IKK, BRAF, RAF1, SRC, AKT), cell cycle regulatory factors (such as CDK4, CDK6, Cyclin D, PLK1, BIRC5), transcription regulatory factors (such as HIF-1α, p53, androgen receptor, estrogen receptor, progesterone receptor) are known (Non-Patent Documents 2, 3). HSP90 is closely related to cell proliferation and survival by maintaining the normal functions of these proteins. Furthermore, HSP90 is required for the normal functioning of mutant or chimeric factors that cause carcinogenesis or cancer progression (e.g., BCR-ABL, NPM-ALK), and thus HSP90 is particularly important in the processes of carcinogenesis, cancer survival, growth, progression, and metastasis (Non-Patent Document 2).

[0003] Currently, various HSP90 inhibitors have been reported as antitumor agents. Patent Document 1 discloses Compound 1 having excellent HSP90 inhibitory action and exhibiting antitumor activity. Patent Documents 2 to 6 disclose uses of Compound 1 and uses in combination with other anticancer agents. Patent Document 7 discloses a crystalline polymorph of Compound 1.

[0004] Generally, pharmaceutical compositions for oral administration are required to have not only stability of the active ingredient but also excellent disintegrability and bioavailability during oral administration.

[0005] However, there are various methods for solving the above problems depending on the structure and properties of the active ingredient, the type of preparation, etc., so it is not easy to find an optimal preparation formula with excellent disintegration and bioavailability.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: International Publication No. 2011 / 004610

[0009] Patent Document 2: International Publication No. 2015 / 046498

[0010] Patent Document 3: International Publication No. 2019 / 004417

[0011] Patent Document 4: International Publication No. 2019 / 054465

[0012] Patent Document 5: International Publication No. 2019 / 220512

[0013] Patent Document 6: International Publication No. 2019 / 221086

[0014] Patent Document 7: International Publication No. 2016 / 181990

[0015] Non-patent literature

[0016] Non-patent document 1: Nat. Rev. Cancer, 5: 761-772 (2005)

[0017] Non-patent document 2: TRENDS Mol. Med., 10: 283-290 (2004)

[0018] Non-patent document 3: Clin Can Res 15, 9-14 (2009) Summary of the invention

[0019] Technical problem to be solved by the invention

[0020] Compound 1 is a compound having excellent HSP90 inhibitory effect and anti-tumor activity. Therefore, the present invention provides a pharmaceutical composition containing Compound 1, which has excellent disintegrability and bioavailability.

[0021] Technical solutions for solving technical problems

[0022] The inventors of the present invention have conducted various studies on manufacturing methods for pharmaceutical compositions containing Compound 1 or a pharmaceutically acceptable salt thereof, and have conducted various studies on the disintegration and bioavailability of Compound 1 or a pharmaceutically acceptable salt thereof by adding various compounds, and have found that Compound 1 is prone to tableting problems such as sticking when using a direct tableting method, which is believed to be caused by the characteristics of Compound 1. Furthermore, as a result of further studies, it has been found that a pharmaceutical composition having excellent disintegration and bioavailability can be obtained by granulating Compound 1 or a pharmaceutically acceptable salt thereof, adding a predetermined crystalline cellulose to the granules, and then tableting.

[0023] That is, the present invention relates to the following [1] to

[17] .

[0024] [1] A pharmaceutical composition comprising a granulated material and crystalline cellulose, wherein the granulated material contains 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof, and wherein the pharmaceutical composition has a disintegration time of not more than 360 seconds in the form of a coated tablet.

[0025] [2] A pharmaceutical composition obtained by mixing a granulated material and 20.0 to 55.0% by mass of crystalline cellulose, wherein the granulated material contains 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof, and the crystalline cellulose before mixing has an L / D ratio of 1.00 to 4.00 and / or a bulk density of 0.20 to 0.50 g / cm 3 .

[0026] [3] A pharmaceutical composition comprising: a granulated material containing 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof; and 20.0 to 55.0% by mass of crystalline cellulose, the crystalline cellulose being selected from Ceolus PH-102, PH-302, KG-802 and UF-711.

[0027] [4] The pharmaceutical composition according to [2] or [3], wherein the content of the crystalline cellulose is 30.0 to 55.0% by mass.

[0028] [5] The pharmaceutical composition according to any one of [2] to [4], which has a disintegration time of 180 seconds or less in the form of an uncoated tablet, or has a disintegration time of 360 seconds or less in the form of a coated tablet.

[0029] [6] A pharmaceutical composition as described in any one of [1] to [5], wherein the additives other than crystalline cellulose added to the granulated material are only additives selected from the group consisting of binders, lubricants, fluidizers, colorants, aromas, flavoring agents, sweeteners, glossing agents, and plasticizers.

[0030] [7] The pharmaceutical composition according to any one of [1] to [5], wherein the additive other than crystalline cellulose added to the granulated material is only a lubricant.

[0031] [8] The pharmaceutical composition according to any one of [1] to [7], comprising 18.0 to 40.0% by mass of 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof.

[0032] [9] The pharmaceutical composition according to any one of [1] to [8], wherein the granulated material is a granulated material produced by a wet granulation method.

[0033]

[10] The pharmaceutical composition according to any one of [1] to [9], wherein the average particle size (d50) of the granulated material is 50 to 400 μm.

[0034]

[11] The pharmaceutical composition according to any one of [1] to

[10] , wherein the solid preparation is preferably a solid preparation for oral administration.

[0035]

[12] The pharmaceutical composition as described in

[11] , which is a tablet.

[0036]

[13] The pharmaceutical composition as described in

[12] , which has a diameter of 6.5 to 9.5 mm.

[0037]

[14] A coating composition obtained by coating the pharmaceutical composition according to any one of [1] to

[13] .

[0038]

[15] A method for producing a pharmaceutical composition, comprising: a step of granulating a powder using a binding liquid, the powder comprising 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propane-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof; and a step of mixing the granulated material obtained in the step with crystalline cellulose so that the content of the crystalline cellulose in the pharmaceutical composition is 20.0 to 55.0% by mass, the crystalline cellulose having an L / D ratio of 1.00 to 4.00 and / or a bulk density of 0.20 to 0.50 g / cm 3 .

[0039]

[16] The method for producing a pharmaceutical composition according to

[15] , wherein the granulation method is a fluidized bed granulation method.

[0040]

[17] A pharmaceutical composition prepared by the method described in

[15] or

[16] .

[0041] In addition, the present invention relates to the following

[18] to

[54] .

[0042]

[18] The pharmaceutical composition according to any one of [1] to

[13] , or the coating composition according to

[14] , which is used for treating a tumor.

[0043]

[19] Use of a pharmaceutical composition comprising a granulated material containing 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof and crystalline cellulose, the composition having a disintegration time of not more than 360 seconds in the form of a coated tablet, for the manufacture of a pharmaceutical for the treatment of tumors.

[0044]

[20] Use of a pharmaceutical composition obtained by mixing a granulated material containing 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propane-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof with 20.0 to 55.0% by mass of crystalline cellulose for the manufacture of a pharmaceutical for treating tumors, wherein the crystalline cellulose before mixing has an L / D ratio of 1.00 to 4.00 and / or a bulk density of 0.20 to 0.50 g / cm 3 .

[0045]

[21] Use of a pharmaceutical composition comprising a granulated material containing 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof and 20.0 to 55.0 mass % of crystalline cellulose selected from Ceolus PH-102, PH-302, KG-802 and UF-711 for the manufacture of a pharmaceutical for the treatment of tumors.

[0046]

[22] The use according to

[20] or

[21] , wherein the content of the crystalline cellulose in the pharmaceutical composition is 30.0 to 55.0% by mass.

[0047]

[23] The use according to any one of

[20] to

[22] , wherein the pharmaceutical composition has a disintegration time of 180 seconds or less in the form of an uncoated tablet, or has a disintegration time of 360 seconds or less in the form of a coated tablet.

[0048]

[24] The use according to any one of

[19] to

[23] , wherein the pharmaceutical composition contains 18.0 to 40.0% by mass of 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof.

[0049]

[25] The use according to any one of

[19] to

[24] , wherein the granulated material is a granulated material produced by a wet granulation method.

[0050]

[26] The use according to any one of

[19] to

[25] , wherein the average particle size (d50) of the granulated material is 50 to 400 μm.

[0051]

[27] The use according to any one of

[19] to

[26] , wherein the pharmaceutical composition is a solid preparation, preferably a solid preparation for oral administration.

[0052]

[28] The use according to any one of

[19] to

[27] , wherein the pharmaceutical composition is a tablet.

[0053]

[29] The use as described in

[28] , wherein the diameter of the tablet is 6.5 to 9.5 mm.

[0054]

[30] The use according to any one of

[19] to

[29] , wherein the pharmaceutical composition is a coated composition obtained by coating the pharmaceutical composition.

[0055]

[31] A pharmaceutical composition for treating a tumor, comprising a granulated material and crystalline cellulose, wherein the granulated material contains 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof, and wherein the pharmaceutical composition has a disintegration time of not more than 360 seconds in the form of a coated tablet.

[0056]

[32] A pharmaceutical composition for treating a tumor, which is obtained by mixing a granulated material and 20.0 to 55.0% by mass of crystalline cellulose, wherein the granulated material contains 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propane-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof, and the crystalline cellulose before mixing has an L / D ratio of 1.00 to 4.00 and / or a bulk density of 0.20 to 0.50 g / cm 3 .

[0057]

[33] A pharmaceutical composition for treating tumors, comprising: a granulated material containing 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propane-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof; and 20.0 to 55.0% by mass of crystalline cellulose, the crystalline cellulose being selected from Ceolus PH-102, PH-302, KG-802 and UF-711.

[0058]

[34] The pharmaceutical composition according to

[32] or

[33] , wherein the content of the crystalline cellulose is 30.0 to 55.0% by mass.

[0059]

[35] The pharmaceutical composition according to any one of

[32] to

[34] , which has a disintegration time of 180 seconds or less in the form of an uncoated tablet, or has a disintegration time of 360 seconds or less in the form of a coated tablet.

[0060]

[36] The pharmaceutical composition according to any one of

[31] to

[35] , comprising 18.0 to 40.0% by mass of 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof.

[0061]

[37] The pharmaceutical composition according to any one of

[31] to

[36] , wherein the granulated material is a granulated material produced by a wet granulation method.

[0062]

[38] The pharmaceutical composition according to any one of

[31] to

[37] , wherein the average particle size (d50) of the granulated material is 50 to 400 μm.

[0063]

[39] The pharmaceutical composition according to any one of

[31] to

[38] , which is a solid preparation, preferably a solid preparation for oral administration.

[0064]

[40] The pharmaceutical composition according to any one of

[31] to

[39] , which is a tablet.

[0065]

[41] The pharmaceutical composition as described in

[40] , which has a diameter of 6.5 to 9.5 mm.

[0066]

[42] The pharmaceutical composition according to any one of

[31] to

[41] , which is a coated composition obtained by coating the pharmaceutical composition.

[0067]

[43] A method for treating tumors, comprising the step of administering an effective amount of a pharmaceutical composition to a subject in need of the pharmaceutical composition, wherein the pharmaceutical composition comprises a granulated material containing 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof and crystalline cellulose, and has a disintegration time of not more than 360 seconds in the form of a coated tablet.

[0068]

[44] A method for treating a tumor, comprising: administering an effective amount of a pharmaceutical composition to a subject in need thereof, wherein the pharmaceutical composition is obtained by mixing a granulated material containing 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof with 20.0 to 55.0% by mass of crystalline cellulose, wherein the crystalline cellulose has an L / D ratio of 1.00 to 4.00 and / or a bulk density of 0.20 to 0.50 g / cm before mixing. 3 .

[0069]

[45] A method for treating a tumor, comprising: a step of administering an effective amount of a pharmaceutical composition to a subject in need of the pharmaceutical composition, wherein the pharmaceutical composition comprises a granulated material containing 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof and 20.0 to 55.0% by mass of crystalline cellulose selected from Ceolus PH-102, PH-302, KG-802 and UF-711.

[0070]

[46] The method according to

[44] or

[45] , wherein the content of the crystalline cellulose in the pharmaceutical composition is 30.0 to 55.0% by mass.

[0071]

[47] The method according to any one of

[44] to

[46] , wherein the pharmaceutical composition has a disintegration time of 180 seconds or less in the form of an uncoated tablet, or has a disintegration time of 360 seconds or less in the form of a coated tablet.

[0072]

[48] ​​The method according to any one of

[43] to

[47] , wherein the pharmaceutical composition contains 18.0 to 40.0% by mass of 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof.

[0073]

[49] The method according to any one of

[43] to

[48] , wherein the granulated material is obtained by a wet granulation method.

[0074]

[50] The method according to any one of

[43] to

[49] , wherein the average particle size (d50) of the granulated material is 50 to 400 μm.

[0075]

[51] The method according to any one of

[43] to

[50] , wherein the pharmaceutical composition is a solid preparation, preferably a solid preparation for oral administration.

[0076]

[52] The method according to any one of

[43] to

[51] , wherein the pharmaceutical composition is a tablet.

[0077]

[53] The method as described in

[52] , wherein the diameter of the tablet is 6.5 to 9.5 mm.

[0078]

[54] The method according to any one of

[43] to

[53] , wherein the pharmaceutical composition is a coated composition obtained by coating the pharmaceutical composition.

[0079] Effects of the Invention

[0080] According to the present invention, a pharmaceutical composition can be provided, which contains Compound 1 or a pharmaceutically acceptable salt thereof, has excellent disintegrability and bioavailability, and has no tableting problems such as adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] Figure 1 The results of measuring the bulk density and major / minor diameter ratio of various crystalline celluloses are shown.

[0082] Figure 2 Indicates the results of the dog absorption experiment. DETAILED DESCRIPTION

[0083] Hereinafter, the pharmaceutical composition and the method for producing the same according to the present invention will be described. However, the pharmaceutical composition and the method for producing the same according to the present invention should not be construed as being limited to the following embodiments and examples.

[0084] [Pharmaceutical composition]

[0085] The pharmaceutical composition of the present invention comprises a granulated material containing 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide (Compound 1) or a pharmaceutically acceptable salt thereof and a predetermined crystalline cellulose.

[0086] In the present invention, 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide is also known as Pimitespib and is a compound having the following structure.

[0087]

[0088] Compound 1 or a pharmaceutically acceptable salt thereof is a known compound and can be synthesized according to the method described in Patent Document 1 (International Publication No. 2011 / 004610), for example.

[0089] When Compound 1 has isomers such as optical isomers, stereoisomers, rotational isomers, and tautomers, all isomers and mixtures thereof are included in Compound 1 unless otherwise specified.

[0090] In addition, Compound 1 or a pharmaceutically acceptable salt thereof may be a solvate (eg, a hydrate, etc.) or a non-solvate, and in the present invention, both are included in “Compound 1 or a pharmaceutically acceptable salt thereof”.

[0091] Pharmaceutically acceptable salts refer to salts of compounds that have the desired pharmacological activity and are prepared from pharmaceutically acceptable non-toxic bases or acids including inorganic or organic bases and inorganic or organic acids.

[0092] The pharmaceutically acceptable salt of Compound 1 is not particularly limited, and examples thereof include addition salts with inorganic acids such as hydrochloric acid and sulfuric acid, organic acids such as acetic acid, citric acid, tartaric acid, and maleic acid, salts with alkali metals such as potassium and sodium, salts with alkaline earth metals such as calcium and magnesium, and salts with organic bases such as ammonium salts, ethylamine salts, and arginine salts.

[0093] Direct tableting is the simplest tableting method, but when compound 1 is tableted by direct tableting, tableting problems occur that are believed to be caused by the characteristics of compound 1. As a solution to this problem, granulation for tableting has been studied. Since the characteristics of the compound are different in each compound, it is difficult to determine which method can be implemented in each compound, and it is not easy to find the most suitable tableting method. However, by granulating compound 1 or a pharmaceutically acceptable salt thereof, adding a specified crystalline cellulose to the granules for tableting, as shown in the examples described later, the above-mentioned problems can be overcome, and tablets with excellent disintegrability are successfully provided.

[0094] In the present invention, the granulated material containing compound 1 or a pharmaceutically acceptable salt thereof is not particularly limited, and may be a wet granulated material or a dry granulated material. The dry granulation method does not use a binder, so it has the characteristic that it can also granulate a drug that is unstable in water, but there is a tendency for the tablet to be large. Therefore, from the perspective of making tablets as small as possible, the granulated material containing compound 1 or a pharmaceutically acceptable salt thereof is preferably a wet granulated material.

[0095] The granulated material containing compound 1 or its pharmaceutically acceptable salt in the present invention may contain active ingredients other than compound 1 or its pharmaceutically acceptable salt, and additives commonly used in pharmaceutical preparations as long as the effect of the present invention can be exerted. It is preferably a granulated material containing only compound 1 or its pharmaceutically acceptable salt as an active ingredient. The content of the additive can be appropriately set within the range that does not impair the purpose of the present invention.

[0096] The granulated material may contain, for example, an excipient, a binder, a disintegrant, a fluidizer, a solubilizer, and the like as additives.

[0097] Examples of excipients in the granulated material include sugar alcohols such as D-mannitol, erythritol, D-sorbitol, and xylitol, trehalose hydrate, β-cyclodextrin, corn starch, sucrose, lactose, crystalline cellulose, anhydrous calcium hydrogen phosphate, precipitated calcium carbonate, etc. Among them, lactose, D-mannitol, crystalline cellulose, corn starch, or a combination thereof are preferred, and lactose, corn starch, or a combination thereof are more preferred.

[0098] Examples of the binder in the granulated material include hydroxypropyl cellulose, hypromellose, povidone, and polyvinyl alcohol, etc. Among them, hydroxypropyl cellulose, povidone, or a combination thereof is preferred, and hydroxypropyl cellulose is more preferred.

[0099] A preferred embodiment of the granulated material containing compound 1 or a pharmaceutically acceptable salt thereof of the present invention is a granulated material comprising compound 1 or a pharmaceutically acceptable salt thereof and one or more additives selected from lactose, D-mannitol, crystalline cellulose, corn starch, hydroxypropyl cellulose and povidone, more preferably a granulated material comprising compound 1 or a pharmaceutically acceptable salt thereof and one or more additives selected from lactose, corn starch and hydroxypropyl cellulose, and particularly preferably a granulated material comprising compound 1 or a pharmaceutically acceptable salt thereof, lactose, corn starch and hydroxypropyl cellulose.

[0100] In addition, another preferred embodiment of the granulated material containing Compound 1 or a pharmaceutically acceptable salt thereof of the present invention is a granulated material containing only Compound 1 or a pharmaceutically acceptable salt thereof as an active ingredient and containing one or more additives selected from lactose, D-mannitol, crystalline cellulose, corn starch, hydroxypropyl cellulose and povidone. It is more preferred to be a granulated material consisting of Compound 1 or a pharmaceutically acceptable salt thereof and one or more additives selected from lactose, D-mannitol, crystalline cellulose, corn starch, hydroxypropyl cellulose and povidone. It is more preferred to be a granulated material consisting of Compound 1 or a pharmaceutically acceptable salt thereof and one or more additives selected from lactose, corn starch and hydroxypropyl cellulose. It is particularly preferred to be a granulated material consisting of Compound 1 or a pharmaceutically acceptable salt thereof, lactose, corn starch and hydroxypropyl cellulose.

[0101] In the pharmaceutical composition of the present invention, taking into account the solubility, stability, absorbability and operability in mass production, the total amount of the pharmaceutical composition is set to 100.0% by mass, and the content of Compound 1 or a pharmaceutically acceptable salt thereof is preferably 18.0 to 40.0% by mass, more preferably 20.0 to 32.0% by mass, more preferably 20.0 to 29.0% by mass, further preferably 26.0 to 29.0% by mass, particularly preferably 26.0 to 27.0% by mass, and most preferably 26.7% by mass.

[0102] The average particle size of the granules containing Compound 1 or its pharmaceutically acceptable salt in the present invention is not particularly limited as long as the effect of the present invention can be exerted. However, if it is too small, the properties of the tablets will be affected, and the possibility of causing tableting problems such as adhesion will increase. If it is too large, the possibility of content deviation in the tablets will increase. The preferred average particle size is the median diameter (particle size with a cumulative frequency of 50%: d 50 ) is 50 to 400 μm, more preferably 50 to 300 μm, more preferably 50 to 250 μm, more preferably 50 to 200 μm, more preferably 60 to 180 μm, more preferably 60 to 150 μm, and particularly preferably 80 to 120 μm. In addition, the median diameter of the granulated material can be measured by a known measuring means, for example, by a sieving method or a laser diffraction particle size distribution measuring method (wet or dry).

[0103] As shown in the examples described below, as an excipient added to the granules containing Compound 1 or a pharmaceutically acceptable salt thereof, lactose, crystalline cellulose and D-mannitol, which are excipients commonly used in preparations in the pharmaceutical field, were compared and studied, and it was found that from the perspective of tablet hardness, moldability and disintegration, the specified crystalline cellulose is preferred. In particular, its disintegration is excellent. Therefore, the excipient added to the granules in the pharmaceutical composition of the present invention includes crystalline cellulose.

[0104] In the present invention, the crystalline cellulose added in addition to the granulated material preferably has a bulk density of 0.20 to 0.50 g / cm 3 From the viewpoint of disintegration, the bulk density of crystalline cellulose is more preferably 0.20 to 0.44 g / cm 3 , particularly preferably 0.25 to 0.44 g / cm 3 .

[0105] The bulk density is 0.20 to 0.50 g / cm 3 As the crystalline cellulose, commercial products can be used, and specifically, Ceolus (registered trademark) PH-102, PH-302, KG-802, UF-711 (all manufactured by Asahi Kasei Corporation) and the like can be used. As the type of crystalline cellulose, Ceolus PH-102, PH-302, KG-802, and UF-711 are preferred, Ceolus PH-102 and PH-302 are more preferred, and Ceolus PH-102 is particularly preferred.

[0106] In addition, "bulk density" refers to the density of a container of a certain volume filled with powder, with its internal volume as the volume, which can be measured by the bulk density and tap density measurement methods specified in the Japanese Pharmacopoeia. The measurement of bulk density will vary to some extent depending on the measurement conditions such as humidity during the measurement. Therefore, its numerical value should not be strictly interpreted. Therefore, in this specification, the numerical value of bulk density can have a value of ±0.08g / cm 3 The measurement error of the range of degrees.

[0107] In the present invention, "L / D ratio" refers to the ratio of the major diameter to the minor diameter of the particles of crystalline cellulose. For example, the L / D ratio can be obtained by measuring the major diameter and the minor diameter of 50 particles using an electron microscope (VHX-D500, manufactured by KEYENCE Co., Ltd.) and calculating the ratio of the average values. In this specification, the numerical value of the L / D ratio may have a measurement error in the range of ±5%.

[0108] In the present invention, the crystalline cellulose added to the granules preferably has an L / D ratio of 1.00 to 4.00. From the viewpoint of disintegrability, the L / D ratio of the crystalline cellulose is more preferably 1.00 to 3.50, more preferably 1.50 to 3.50, more preferably 1.62 to 3.50, and particularly preferably 1.62 to 3.15.

[0109] As crystalline cellulose having an L / D ratio of 1.00 to 4.00, commercially available products can be used, and specifically, Ceolus (registered trademark) PH-102, PH-302, KG-802, UF-711 (all manufactured by Asahi Kasei Corporation) etc. can be used. As the type of crystalline cellulose, Ceolus PH-102, PH-302, KG-802, UF-711 are preferred, Ceolus PH-102, PH-302 are more preferred, and Ceolus PH-102 is particularly preferred.

[0110] In the pharmaceutical composition of the present invention, from the viewpoint of disintegration properties, the content of crystalline cellulose added other than the granulated material is preferably 20.0 to 55.0% by mass, more preferably 30.0 to 55.0% by mass, more preferably 35.0 to 55.0% by mass, further preferably 35.0 to 36.0% by mass, and particularly preferably 35.2% by mass, based on the total amount of the pharmaceutical composition as 100.0% by mass.

[0111] The pharmaceutical composition of the present invention may contain additives commonly used in pharmaceutical preparations other than crystalline cellulose as long as the effects of the present invention can be exhibited.

[0112] Additives other than crystalline cellulose that are added to the granulated material are not particularly limited as long as they are substances commonly used in preparations in the pharmaceutical field. For example, excipients other than crystalline cellulose, binders, disintegrants, lubricants, fluidizing agents, colorants, aromas, flavoring agents, sweeteners, glossing agents, plasticizers, etc. can be listed.

[0113] Examples of the excipient and binder include the above-mentioned excipients and binders.

[0114] In addition, examples of disintegrants include low-substituted hydroxypropyl cellulose, carmellose, corn starch, carmellose sodium, croscarmellose sodium, carmellose calcium, partially pregelatinized starch, crospovidone, etc. Among them, croscarmellose sodium, carmellose calcium, partially pregelatinized starch, crospovidone, or a combination thereof are preferred, and croscarmellose sodium is particularly preferred.

[0115] Examples of lubricants include hydrogenated oil, sucrose fatty acid esters, sodium lauryl sulfate, magnesium stearate, sodium stearyl fumarate, and stearic acid. Among them, magnesium stearate, stearic acid, or a combination thereof is preferred, and magnesium stearate is particularly preferred.

[0116] In addition, examples of coloring agents include food yellow No. 5 pigment, food blue No. 2 pigment, food lake pigment, ferric oxide, yellow ferric oxide, and titanium oxide, etc. Among them, titanium oxide is preferred.

[0117] Examples of the fluidizing agent include light silicic anhydride, hydrous silicon dioxide, talc, and magnesium stearate.

[0118] A preferred embodiment of the additives other than crystalline cellulose added to the granulated material in the pharmaceutical composition of the present invention is that it does not contain excipients other than crystalline cellulose (that is, the excipient added to the granulated material is only crystalline cellulose), and specifically, it contains only additives selected from binders, disintegrants, lubricants, fluidizers, colorants, aromas, flavors, sweeteners, glossing agents, and plasticizers. It is more preferred that it does not contain excipients other than crystalline cellulose and disintegrants. Specifically, it contains only additives selected from binders, lubricants, fluidizers, colorants, aromas, flavors, sweeteners, glossing agents, and plasticizers, and it is particularly preferred that it contains only lubricants.

[0119] The pharmaceutical composition of the present invention can be in the form of various preparations, preferably in the form of solid preparations, and particularly preferably in the form of solid preparations for oral administration. As solid preparations, for example, tablets (including uncoated tablets, orally disintegrating tablets, chewable tablets, etc.), capsules (including soft capsules, hard capsules, etc.), granules, powders, and pills can be cited, preferably tablets, and particularly preferably uncoated tablets.

[0120] The pharmaceutical composition of the present invention is expected to be used as an anti-tumor agent and is a highly active substance. From the perspective of hazard countermeasures and edibility, it is preferred to apply a coating on the surface of the pharmaceutical composition of the present invention to form a coated composition. Here, the coating is not particularly limited as long as it can prevent the active ingredients in the uncoated tablet from being exposed on the surface, and includes film coating and sugar coating, etc., preferably film coating. Uncoated tablets refer to tablets on which no coating is applied to the surface of the tablets obtained by tableting, and coated tablets refer to tablets on which a coating is applied to the surface of the uncoated tablets.

[0121] As coating bases, hydroxypropyl methylcellulose, ethyl cellulose, hydroxypropyl cellulose, polyvinyl alcohol, polyethylene glycol, white sugar, etc. can be cited. Among them, hydroxypropyl methylcellulose, polyethylene glycol or a combination thereof is preferred. In addition, coating additives can also be used in the coating. As coating additives, for example, sunscreens, fluidizers, colorants, fragrances, plasticizers, etc. can be cited.

[0122] Compound 1 has excellent HSP90 inhibitory effect and anti-tumor activity, so the pharmaceutical composition of the present invention is useful as a pharmaceutical composition for the prevention or treatment of tumors. Tumors are tumors in which compound 1 or a pharmaceutically acceptable salt thereof exerts an anti-tumor effect, and more preferably malignant tumors in which HSP90 is involved. Specifically, head and neck cancer, digestive system cancer (esophageal cancer, gastric cancer, duodenal cancer, liver cancer, biliary cancer (gallbladder / bile duct cancer, etc.), pancreatic cancer, small intestine cancer, large intestine cancer (colorectal cancer, colon cancer, rectal cancer, etc.), gastrointestinal stromal tumors, etc.), lung cancer (non-small cell lung cancer, small cell lung cancer), breast cancer, ovarian cancer, uterine cancer (cervical cancer, endometrial cancer, etc.), kidney cancer, bladder cancer, prostate cancer, skin cancer, etc. can be cited.

[0123] The size of pharmaceutical compositions for oral administration is a big problem for elderly people with impaired swallowing function, and providing small and easy-to-swallow preparations will help improve the compliance of the elderly. On the other hand, in order to achieve excellent disintegration and tablet hardness, it is necessary to add sufficient excipients, binders, disintegrants and lubricants according to the characteristics of the active ingredients. Therefore, it is difficult to achieve miniaturization of tablets while achieving excellent disintegration and tablet hardness. Generally speaking, when the diameter is 10 mm, the swallowing function of the subject needs to be considered, and when the diameter is 6 mm, it is considered difficult for the elderly to operate because it is too small (Journal of the Japanese Geriatrics Society Vol. 44 No. 5 627-633 (2007: 9)).

[0124] From the above, from the viewpoint of easy administration and easy grasping, the diameter of the pharmaceutical composition of the present invention is preferably 6.5 to 9.5 mm, more preferably 7.0 to 9.0 mm, and particularly preferably 7.0 to 8.0 mm.

[0125] In addition, the "diameter" in the present invention refers to a diameter in the general sense in the case of a circular tablet, and refers to a major diameter in the case of an elliptical tablet such as an oval tablet. The diameter of a tablet can be measured by a generally known measurement method.

[0126] In addition, the disintegration time of the pharmaceutical composition of the present invention is preferably within 180 seconds, more preferably within 120 seconds in an uncoated tablet. It is preferably within 360 seconds, more preferably within 300 seconds in a coated tablet. As shown in the examples described below, such an excellent disintegration time can be achieved by adding a specific amount of specific crystalline cellulose to the granulated material of the present invention.

[0127] The "disintegration time" can be measured, for example, by the disintegration test method specified in the Japanese Pharmacopoeia. In addition, depending on the dosage form to be measured, it can be measured by the disintegration test method for tablets or coatings specified in the Japanese Pharmacopoeia. More specifically, a disintegration tester can be used, and the test liquid is water (37±2°C) and there is no disk, and the time from the tablet being put into the tester to the tablet being completely disintegrated can be measured.

[0128] As a preferred embodiment of the disintegration time of the pharmaceutical composition of the present invention, the disintegration time measured by the disintegration test method specified in the Japanese Pharmacopoeia is preferably within 180 seconds in the state of an uncoated tablet, and more preferably within 120 seconds. The disintegration time measured by the disintegration test method specified in the Japanese Pharmacopoeia is preferably within 360 seconds in the state of a coated tablet, and more preferably within 300 seconds.

[0129] As another preferred embodiment of the disintegration time of the pharmaceutical composition of the present invention, the disintegration time measured from the time when the tablet is put into the tester to the time when the tablet is completely disintegrated using a disintegration tester under the conditions of the test liquid: water (37±2°C) and no disk is preferably within 180 seconds, more preferably within 120 seconds, in the state of an uncoated tablet. The disintegration time measured from the time when the tablet is put into the tester to the time when the tablet is completely disintegrated using a disintegration tester under the conditions of the test liquid: water (37±2°C) and no disk is preferably within 360 seconds, more preferably within 300 seconds, in the state of a coated tablet.

[0130] In view of moldability and the possibility of failure during transportation, the hardness of the pharmaceutical composition of the present invention is 50 N or more, preferably 60 N or more, more preferably 70 N or more, and even more preferably 80 N or more.

[0131] "Hardness" is a well-known standard in the pharmaceutical field. For example, in the case of tablets, a tablet hardness tester (e.g., PC-30, manufactured by Okada Seiko Co., Ltd., 8M, Schleuniger) can be used to slowly apply pressure to the tablet from the lateral side of the tablet, and the load (N) at the moment when the tablet breaks can be measured.

[0132] The pharmaceutical composition of the present invention has excellent disintegration properties, and therefore, has sufficient bioavailability in the patient's body to achieve drug efficacy. Here, "bioavailability" is an index indicating how much of the drug circulates in the body after administration, and refers to the proportion of compound 1 in the body circulation of the pharmaceutical composition containing compound 1 after oral administration. Bioavailability can be measured by absorbability in dog pharmacokinetics, for example, as shown in the examples described below.

[0133] A preferred embodiment of the pharmaceutical composition of the present invention is a pharmaceutical composition comprising a granulated material containing Compound 1 or a pharmaceutically acceptable salt thereof and crystalline cellulose, and having a disintegration time of within 360 seconds in the form of a coated tablet;

[0134] More preferably, the pharmaceutical composition comprises a granulated material containing only Compound 1 or a pharmaceutically acceptable salt thereof as an active ingredient and crystalline cellulose, and contains no excipients other than crystalline cellulose as an additive other than crystalline cellulose added to the granulated material, and has a disintegration time of 360 seconds or less in the state of a coated tablet;

[0135] More preferably, the pharmaceutical composition comprises a granulated material and crystalline cellulose, wherein the granulated material contains only Compound 1 or a pharmaceutically acceptable salt thereof as an active ingredient, and contains one or more additives selected from lactose, D-mannitol, crystalline cellulose, corn starch, hydroxypropyl cellulose and povidone, and the additive other than crystalline cellulose added to the granulated material does not contain an excipient other than crystalline cellulose, and has a disintegration time of 360 seconds or less in the state of a coated tablet;

[0136] Particularly preferred is a pharmaceutical composition consisting of a granulated material, crystalline cellulose and a lubricant, wherein the granulated material consists of Compound 1 or a pharmaceutically acceptable salt thereof, lactose, corn starch and hydroxypropyl cellulose, and the pharmaceutical composition has a disintegration time of less than 360 seconds in the form of a coated tablet.

[0137] A preferred embodiment of the pharmaceutical composition of the present invention is a pharmaceutical composition comprising a granulated material containing Compound 1 or a pharmaceutically acceptable salt thereof and crystalline cellulose, wherein the disintegration time measured by the disintegration test method specified in the Japanese Pharmacopoeia is within 360 seconds in the state of a coated tablet;

[0138] More preferably, it is a pharmaceutical composition containing a granulated material containing only Compound 1 or a pharmaceutically acceptable salt thereof as an active ingredient and crystalline cellulose, and the additive other than crystalline cellulose added to the granulated material does not contain an excipient other than crystalline cellulose, and the disintegration time measured by the disintegration test method specified in the Japanese Pharmacopoeia is within 360 seconds in the state of a coated tablet;

[0139] More preferably, it is a pharmaceutical composition comprising a granulated material and crystalline cellulose, wherein the granulated material contains only Compound 1 or a pharmaceutically acceptable salt thereof as an active ingredient, and contains one or more additives selected from lactose, D-mannitol, crystalline cellulose, corn starch, hydroxypropyl cellulose and povidone, and the additive other than crystalline cellulose added to the granulated material does not contain an excipient other than crystalline cellulose, and the disintegration time measured by the disintegration test method specified in the Japanese Pharmacopoeia is within 360 seconds in the state of a coated tablet;

[0140] Particularly preferred is a pharmaceutical composition consisting of a granulated material, crystalline cellulose and a lubricant, wherein the granulated material consists of Compound 1 or a pharmaceutically acceptable salt thereof, lactose, corn starch and hydroxypropyl cellulose, and the disintegration time of the pharmaceutical composition in the form of a coated tablet as measured by the disintegration test method specified in the Japanese Pharmacopoeia is within 360 seconds.

[0141] A preferred embodiment of the pharmaceutical composition of the present invention is a pharmaceutical composition comprising a granulated material containing Compound 1 or a pharmaceutically acceptable salt thereof and crystalline cellulose, wherein the disintegration time measured from the time when the tablet is put into the tester to the time when the tablet is completely disintegrated using a disintegration tester under the conditions of test liquid: water (37±2°C) and no disk is within 360 seconds in the state of a coated tablet;

[0142] More preferably, the pharmaceutical composition comprises a granulated material containing only Compound 1 or a pharmaceutically acceptable salt thereof as an active ingredient and crystalline cellulose, and the additive other than crystalline cellulose added to the granulated material does not contain an excipient other than crystalline cellulose, and the disintegration time measured as the time from the tablet being put into the tester to the tablet being completely disintegrated using a disintegration tester under the conditions of test liquid: water (37±2°C) and no disk is within 360 seconds in the state of a coated tablet;

[0143] More preferably, the granulated material comprises crystalline cellulose, wherein the granulated material contains only Compound 1 or a pharmaceutically acceptable salt thereof as an active ingredient, and contains one or more additives selected from lactose, D-mannitol, crystalline cellulose, corn starch, hydroxypropyl cellulose and povidone, and the additive other than crystalline cellulose added to the granulated material does not contain excipients other than crystalline cellulose, and the disintegration time measured as the time from the tablet being put into the tester to the tablet being completely disintegrated using a disintegration tester under the conditions of the test liquid: water (37±2°C) and no disk is within 360 seconds in the state of a coated tablet;

[0144] Particularly preferred is a pharmaceutical composition consisting of a granulated material, crystalline cellulose and a lubricant, wherein the granulated material consists of compound 1 or a pharmaceutically acceptable salt thereof, lactose, corn starch and hydroxypropyl cellulose, and the pharmaceutical composition uses a disintegration tester, under the conditions of test liquid: water (37±2°C) and no disk, and the disintegration time obtained as the time from the tablet being put into the tester to the complete disintegration of the tablet is within 360 seconds in the state of a coated tablet.

[0145] Another preferred embodiment of the pharmaceutical composition of the present invention is a pharmaceutical composition obtained by mixing a granulated product containing Compound 1 or a pharmaceutically acceptable salt thereof with 20.0 to 55.0% by mass of crystalline cellulose, wherein the L / D ratio of the crystalline cellulose before mixing is 1.00 to 4.00 and / or the bulk density is 0.20 to 0.50 g / cm 3 ;

[0146] More preferably, the pharmaceutical composition is obtained by mixing a granulated product containing only Compound 1 or a pharmaceutically acceptable salt thereof as an active ingredient with 20.0 to 55.0% by mass of crystalline cellulose, wherein the L / D ratio of the crystalline cellulose before mixing is 1.00 to 4.00 and / or the bulk density is 0.20 to 0.50 g / cm 3 , and the additives other than crystalline cellulose added as the granulated material do not contain excipients other than crystalline cellulose;

[0147] More preferably, the pharmaceutical composition is obtained by mixing the granulated material with 20.0 to 55.0% by mass of crystalline cellulose, wherein the granulated material contains only Compound 1 or a pharmaceutically acceptable salt thereof as an active ingredient and contains one or more additives selected from lactose, D-mannitol, crystalline cellulose, corn starch, hydroxypropyl cellulose and povidone, wherein the L / D ratio of the crystalline cellulose before mixing is 1.00 to 4.00 and / or the bulk density is 0.20 to 0.50 g / cm 3 , and the additives other than crystalline cellulose added as the granulated material do not contain excipients other than crystalline cellulose;

[0148] Particularly preferred is a pharmaceutical composition obtained by mixing only 20.0 to 55.0% by mass of crystalline cellulose and a lubricant with a granulated material, wherein the granulated material is composed of Compound 1 or a pharmaceutically acceptable salt thereof, lactose, corn starch and hydroxypropyl cellulose, wherein the L / D ratio of the crystalline cellulose before mixing is 1.00 to 4.00 and / or the bulk density is 0.20 to 0.50 g / cm 3 .

[0149] Another preferred embodiment of the pharmaceutical composition of the present invention is a pharmaceutical composition comprising a granulated material containing Compound 1 or a pharmaceutically acceptable salt thereof and 20.0 to 55.0% by mass of one or more crystalline celluloses selected from Ceolus PH-102, PH-302, KG-802 and UF-711;

[0150] More preferably, it is a pharmaceutical composition comprising a granulated material containing only Compound 1 or a pharmaceutically acceptable salt thereof as an active ingredient and 20.0 to 55.0% by mass of one or more crystalline celluloses selected from Ceolus PH-102, PH-302, KG-802 and UF-711, wherein the additive other than crystalline cellulose added to the granulated material does not contain an excipient other than crystalline cellulose;

[0151] More preferably, it is a pharmaceutical composition comprising a granulated material and 20.0 to 55.0% by mass of one or more crystalline celluloses selected from Ceolus PH-102, PH-302, KG-802 and UF-711, wherein the granulated material contains only Compound 1 or a pharmaceutically acceptable salt thereof as an active ingredient, and contains one or more additives selected from lactose, D-mannitol, crystalline cellulose, corn starch, hydroxypropyl cellulose and povidone, and in the pharmaceutical composition, the additives other than crystalline cellulose added as the granulated material do not contain excipients other than crystalline cellulose;

[0152] Particularly preferred is a pharmaceutical composition consisting of a granulated material, 20.0 to 55.0% by mass of one or more crystalline celluloses selected from Ceolus PH-102, PH-302, KG-802 and UF-711, and a lubricant, wherein the granulated material consists of Compound 1 or a pharmaceutically acceptable salt thereof, lactose, corn starch and hydroxypropyl cellulose.

[0153] [Method for producing pharmaceutical composition]

[0154] The pharmaceutical composition of the present invention can preferably be obtained by the following production method, which comprises: a step of granulating a powder containing Compound 1 or a pharmaceutically acceptable salt thereof using a binding liquid; and a step of mixing the granulated material obtained in the above step with crystalline cellulose in such a manner that the content of the above crystalline cellulose in the pharmaceutical composition becomes 20.0 to 55.0% by mass.

[0155] The powder containing Compound 1 or a pharmaceutically acceptable salt thereof may contain active ingredients other than Compound 1 or a pharmaceutically acceptable salt thereof, and additives commonly used in preparations in the above-mentioned medical field.

[0156] In the present invention, examples of the granulation method include wet granulation methods such as fluidized bed granulation, stirring granulation, tumbling granulation, extrusion granulation, spray granulation, and crushing granulation. Among them, the fluidized bed granulation method is preferred.

[0157] As the binder liquid used for granulation, a solution obtained by dissolving or dispersing the above-mentioned binder in water is preferably mentioned.

[0158] After granulation, the obtained granules may be dried, or the particle size of the granules may be adjusted by a granulator or the like.

[0159] Next, the obtained granulated material is mixed with crystalline cellulose. The crystalline cellulose is as described above.

[0160] Regarding the mixing ratio of the granulated material and the crystalline cellulose, in the pharmaceutical composition, the total amount of the pharmaceutical composition is set to 100.0% by mass, and the content of crystalline cellulose is 20.0 to 55.0% by mass, preferably 30.0 to 55.0% by mass, more preferably 35.0 to 55.0% by mass, further preferably 35.0 to 36.0% by mass, and particularly preferably 35.2% by mass.

[0161] In addition, in the pharmaceutical composition, the content of Compound 1 or a pharmaceutically acceptable salt thereof is preferably 18.0 to 40.0 mass%, more preferably 20.0 to 32.0 mass%, further preferably 20.0 to 29.0 mass%, further preferably 26.0 to 29.0 mass%, particularly preferably 26.0 to 27.0 mass%, and most preferably 26.7 mass%, with the total amount of the pharmaceutical composition being 100.0 mass%.

[0162] In this manner, a pharmaceutical composition comprising a granulated material containing Compound 1 or a pharmaceutically acceptable salt thereof and 20.0 to 55.0% by mass of crystalline cellulose can be obtained.

[0163] The pharmaceutical composition can also be directly taken in the form of granules, powders, etc. In addition, when the pharmaceutical composition is formulated in the form of tablets, it can be manufactured by, for example, mixing the above-mentioned granules and crystalline cellulose and then compressing the tablets. The tableting can be performed using a known tablet press, and the tableting pressure can be appropriately adjusted so that the obtained tablet has a moderate hardness and the pharmaceutical composition can be quickly disintegrated. As the tablet press, for example, a rotary tablet press, a single-head tablet press, a hydraulic tablet press, etc. can be appropriately selected and used.

[0164] Furthermore, the pharmaceutical composition may be coated as necessary. The coating base and coating additive are as described above.

[0165] All publications, patents, and patent applications cited in this specification are incorporated herein by direct reference.

[0166] Next, embodiments are given to explain the present invention in detail, but the present invention is not limited thereto.

[0167] Example

[0168] [Reference Example 1: Production of granulated material]

[0169] 2000 g of pimetribizol (manufactured by Alps Pharmaceutical Co., Ltd.), 1925 g of lactose hydrate (Lactochem fine powder, manufactured by DMV Fonterra Excipients GmbH & Co. KG), and 750 g of corn starch (Nisshoku Cornstarch W, manufactured by Nippon Food Chemical Co., Ltd.) were put into a fluidized bed granulator "FLC-3N-5" (manufactured by Freund Sangyo Co., Ltd.), and 1500 g of a binding liquid obtained by dissolving 300 g of hydroxypropyl cellulose (HPC SSL, manufactured by Nippon Soda Co., Ltd.) in 2700 g of pure water was used for fluidized bed granulation. Granulation was performed using a sieve (mesh size 600 μm) to obtain a granulated product.

[0170] [Reference Example 2: Preparation of Tablet 1]

[0171] 100 g of pimetribizol (manufactured by Alps Pharmaceutical Industry Co., Ltd.), 96.25 g of lactose hydrate (Lactochem fine powder, manufactured by DMV Fonterra Excipients GmbH & Co. KG), and 37.5 g of corn starch (Nisshoku Cornstarch W, manufactured by Nippon Food Chemical Co., Ltd.) were put into a fluidized bed granulator "FL-LABO" (manufactured by Freund Sangyo Co., Ltd.), and 75 g of a binding liquid obtained by dissolving 30 g of hydroxypropyl cellulose (HPC SSL, manufactured by Nippon Soda Co., Ltd.) in 270 g of pure water was used for fluidized bed granulation. Granulation was performed using a sieve (mesh size 600 μm) to obtain a granulated product. To 193 g of the obtained granules, 6 g of cross-linked carboxymethyl cellulose sodium (Ac-Di-Sol SD-711, manufactured by FMC Health and Nutrition) and 1 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and thoroughly mixed. The mixture was pressed using a rotary tablet press "VELAG" (manufactured by Kikusui Seisakusho Co., Ltd.) with a compression force of 5 kN to obtain tablets with a diameter of 6 mm and a mass of 100 mg.

[0172] [Reference Example 3: Preparation of Tablet 2]

[0173] To 1.93 g of the granulated material obtained in Reference Example 1, 1 g of lactose hydrate (Supertab 11SD, manufactured by DMV Fonterra Excipients GmbH & Co. KG), 0.06 g of cross-linked carboxymethyl cellulose sodium (Ac-Di-Sol SD-711, manufactured by FMC Health and Nutrition), and 0.01 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and thoroughly mixed. The mixture was pressed using a hydraulic tablet press (manufactured by Riken Seiki Co., Ltd.) with a compression force of 0.75 ton to obtain tablets with a diameter of 7 mm and a mass of 150 mg.

[0174] [Reference Example 4: Preparation of Tablet 3]

[0175] To 1.93 g of the granulated material obtained in Reference Example 1, 1 g of crystalline cellulose (Ceolus KG-802, manufactured by Asahi Kasei Corporation), 0.06 g of cross-linked carboxymethyl cellulose sodium (Ac-Di-Sol SD-711, manufactured by FMC Health and Nutrition), and 0.01 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and thoroughly mixed, and tablets were pressed with a compression force of 2 kN using a precision universal testing machine Autograph (manufactured by Shimadzu Corporation) to obtain tablets with a diameter of 7 mm and a mass of 150 mg.

[0176] [Reference Example 5: Preparation of Tablet 4]

[0177] To 1.93 g of the granulated material obtained in Reference Example 1, 1 g of D-mannitol (Pearlitol 100SD, Roquette), 0.06 g of cross-linked carboxymethyl cellulose sodium (Ac-Di-Sol SD-711, manufactured by FMC Health and Nutrition), and 0.01 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and thoroughly mixed, and tablets were pressed with a compression force of 3.5 kN using a precision universal testing machine Autograph (manufactured by Shimadzu Corporation) to obtain tablets with a diameter of 7 mm and a mass of 150 mg.

[0178] [Test Example 1: Measurement of hardness and disintegration time]

[0179] For the tablets prepared in Reference Example 2, the hardness in the diameter direction was measured using a tablet hardness meter (8M, Schleuniger), and the hardness (N) was calculated from the average value of 5 tablets. The disintegration time was measured using a disintegration tester (NT-4H (P), manufactured by Toyama Sangyo Co., Ltd.), under the conditions of test liquid: water (37 ± 2 ° C) and no disk, and the time from the tablet being put into the tester to the tablet being completely disintegrated was measured.

[0180] For the tablets prepared in Reference Example 3, the hardness in the diameter direction was measured using a tablet hardness meter (8M, Schleuniger), and the hardness (N) was calculated from the average value of three tablets. The disintegration time was measured using a disintegration tester (NT-4H, manufactured by Toyama Sangyo Co., Ltd.) under the conditions of test liquid: water (37±2°C) and no disk, and the time from the tablet being put into the tester to the tablet being completely disintegrated was measured.

[0181] For the tablets prepared in Reference Examples 4 and 5, the hardness in the diameter direction was measured using a tablet hardness meter (PC-30, manufactured by Okada Seiko Co., Ltd.), and the hardness (N) was calculated from the average value of three tablets. The disintegration time was measured using a disintegration tester (NT-4H, manufactured by Toyama Sangyo Co., Ltd.) under the conditions of test liquid: water (37±2°C) and no disk, and the time from the tablet being put into the tester to the tablet being completely disintegrated was measured.

[0182] The results are shown in Table 1.

[0183] [Table 1]

[0184]

[0185] According to Table 1, when observing the disintegration behavior, it was found that Reference Example 2 gradually disintegrated from the periphery of the tablet, and it was considered that water was not introduced into the tablet, while in Reference Examples 3, 4, and 5, it was confirmed that the tablet disintegrated into several fragments in the disintegration tester, and it was known that the disintegration time and disintegration behavior can be improved by adding a sufficient amount of excipients during granulation. The formulation was optimized based on Reference Example 4, in which the disintegration time was confirmed to be relatively improved.

[0186] [Example 1: Production of Tablet A]

[0187] To 96.5 g of the granulated material obtained in Reference Example 1, 52.75 g of crystalline cellulose (Ceolus PH-102, manufactured by Asahi Kasei Corporation) and 0.75 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and mixed thoroughly. The mixture was compressed using a rotary tablet press "VELAG" (manufactured by Kikusui Seisakusho Co., Ltd.) with a mass of 150 mg per tablet, 40 mg of pimetribuzin, 52.75 mg of crystalline cellulose (Ceolus PH-102), and a tableting pressure of 4 kN to obtain tablets.

[0188] The tablets were put into a coating machine "HC-FZ-LABO" (manufactured by Freund Sangyo Co., Ltd.) and coated with a coating solution prepared by dissolving 28.8 g of hypromellose (TC-5R, manufactured by Shin-Etsu Chemical Co., Ltd.), 3.6 g of polyethylene glycol 6000 (Macrogol 6000P, manufactured by NOF Corporation) and 3.6 g of titanium oxide (NA63, manufactured by Toho Titanium Co., Ltd.) in 324 g of pure water. The tablets were coated with 150 mg of mass, 3.6 mg of hypromellose, 0.45 mg of polyethylene glycol 6000 and 0.45 mg of titanium oxide per tablet to obtain coated tablets with a diameter of 7.5 mm and a mass of 154.5 mg.

[0189] [Example 2: Production of Tablet B]

[0190] To 96.5 g of the granulated material obtained in Reference Example 1, 52.75 g of crystalline cellulose (Ceolus PH-302, manufactured by Asahi Kasei Corporation) and 0.75 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and mixed thoroughly. The mixture was compressed using a rotary tablet press "VELAG" (manufactured by Kikusui Seisakusho Co., Ltd.) with a mass of 150 mg per tablet, 40 mg of pimetribuzin, 52.75 mg of crystalline cellulose (Ceolus PH-302), and a tableting pressure of 5 kN to obtain tablets.

[0191] The tablets were put into a coating machine "HC-FZ-LABO" (manufactured by Freund Sangyo Co., Ltd.), and coated with a coating solution obtained by dissolving 64.8 g of hypromellose (TC-5R, manufactured by Shin-Etsu Chemical Co., Ltd.), 8.1 g of polyethylene glycol 6000 (Macrogol 6000P, manufactured by NOF Corporation), and 8.1 g of titanium oxide (NA63, manufactured by Toho Titanium Co., Ltd.) in 729 g of pure water. The tablets were coated with 150 mg of mass, 3.6 mg of hypromellose, 0.45 mg of polyethylene glycol 6000, and 0.45 mg of titanium oxide per tablet to obtain coated tablets with a diameter of 7.5 mm and a mass of 154.5 mg.

[0192] [Example 3: Production of Tablet C]

[0193] To 96.5 g of the granulated material obtained in Reference Example 1, 52.75 g of crystalline cellulose (Ceolus KG-802, manufactured by Asahi Kasei Corporation) and 0.75 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and mixed thoroughly. The mixture was compressed using a rotary tablet press "VELAG" (manufactured by Kikusui Seisakusho Co., Ltd.) with a mass of 150 mg per tablet, 40 mg of pimidel, 52.75 mg of crystalline cellulose (Ceolus KG-802), and a tableting pressure of 3 kN to obtain tablets.

[0194] The tablets were put into a coating machine "HC-FZ-LABO" (manufactured by Freund Sangyo Co., Ltd.) and coated with a coating solution prepared by dissolving 28.8 g of hypromellose (TC-5R, manufactured by Shin-Etsu Chemical Co., Ltd.), 3.6 g of polyethylene glycol 6000 (Macrogol 6000P, manufactured by NOF Corporation) and 3.6 g of titanium oxide (NA63, manufactured by Toho Titanium Co., Ltd.) in 324 g of pure water. The tablets were coated with 150 mg of mass, 3.6 mg of hypromellose, 0.45 mg of polyethylene glycol 6000 and 0.45 mg of titanium oxide per tablet to obtain coated tablets with a diameter of 7.5 mm and a mass of 154.5 mg.

[0195] [Example 4: Production of Tablet D]

[0196] To 96.5 g of the granulated material obtained in Reference Example 1, 52.75 g of crystalline cellulose (Ceolus UF-711, manufactured by Asahi Kasei Corporation) and 0.75 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and mixed thoroughly. The mixture was compressed using a rotary tablet press "VELAG" (manufactured by Kikusui Seisakusho Co., Ltd.) with a mass of 150 mg per tablet, 40 mg of pimidel, 52.75 mg of crystalline cellulose (Ceolus UF-711), and a tableting pressure of 3.5 kN to obtain tablets.

[0197] The tablets were put into a coating machine "HC-FZ-LABO" (manufactured by Freund Sangyo Co., Ltd.) and coated with a coating solution prepared by dissolving 28.8 g of hypromellose (TC-5R, manufactured by Shin-Etsu Chemical Co., Ltd.), 3.6 g of polyethylene glycol 6000 (Macrogol 6000P, manufactured by NOF Corporation) and 3.6 g of titanium oxide (NA63, manufactured by Toho Titanium Co., Ltd.) in 324 g of pure water. The tablets were coated with 150 mg of mass, 3.6 mg of hypromellose, 0.45 mg of polyethylene glycol 6000 and 0.45 mg of titanium oxide per tablet to obtain coated tablets with a diameter of 7.5 mm and a mass of 154.5 mg.

[0198] [Comparative Example 1: Production of Tablet a]

[0199] To 96.5 g of the granulated material obtained in Reference Example 1, 52.75 g of crystalline cellulose (Ceolus KG-1000, manufactured by Asahi Kasei Corporation) and 0.75 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and mixed thoroughly. The mixture was compressed using a rotary tablet press "VELAG" (manufactured by Kikusui Seisakusho Co., Ltd.) with a mass of 150 mg per tablet, 40 mg of pimidel, 52.75 mg of crystalline cellulose (Ceolus KG-1000), and a tableting pressure of 3 kN to obtain tablets.

[0200] The tablets were put into a coating machine "HC-FZ-LABO" (manufactured by Freund Sangyo Co., Ltd.) and coated with a coating solution prepared by dissolving 28.8 g of hypromellose (TC-5R, manufactured by Shin-Etsu Chemical Co., Ltd.), 3.6 g of polyethylene glycol 6000 (Macrogol 6000P, manufactured by NOF Corporation) and 3.6 g of titanium oxide (NA63, manufactured by Toho Titanium Co., Ltd.) in 324 g of pure water. The tablets were coated with 150 mg of mass, 3.6 mg of hypromellose, 0.45 mg of polyethylene glycol 6000 and 0.45 mg of titanium oxide per tablet to obtain coated tablets with a diameter of 7.5 mm and a mass of 154.5 mg.

[0201] [Comparative Example 2: Production of Tablet b]

[0202] To 125.45 g of the granulated material obtained in Reference Example 1, 0.62 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) was added and mixed thoroughly, and tablets were obtained using a rotary tablet press "VELAG" (manufactured by Kikusui Seisakusho Co., Ltd.) with a mass of 96.98 mg per tablet, 40 mg of pimidylpidem, and a tableting pressure of 4 kN.

[0203] The tablets were put into a coating machine "HC-FZ-LABO" (manufactured by Freund Sangyo Co., Ltd.), and coated with a coating solution obtained by dissolving 23.3 g of hypromellose (TC-5R, manufactured by Shin-Etsu Chemical Co., Ltd.), 2.9 g of polyethylene glycol 6000 (Macrogol 6000P, manufactured by NOF Corporation), and 2.9 g of titanium oxide (Titanium oxide NA63, manufactured by Toho Titanium Industry Co., Ltd.) in 261.8 g of pure water. The tablets were coated with 96.98 mg of mass, 2.33 mg of hypromellose, 0.29 mg of polyethylene glycol 6000, and 0.29 mg of titanium oxide per tablet to obtain coated tablets with a diameter of 6 mm and a mass of 99.89 mg.

[0204] [Example 5: Production of Tablet E]

[0205] To 96.5 g of the granulated material obtained in Reference Example 1, 27.88 g of crystalline cellulose (Ceolus PH-102, manufactured by Asahi Kasei Corporation) and 0.63 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and mixed thoroughly. The mixture was compressed using a rotary tablet press "VELAG" (manufactured by Kikusui Seisakusho Co., Ltd.) with a mass of 125 mg per tablet, 40 mg of pimidel, 27.875 mg of crystalline cellulose (Ceolus PH-102), and a tableting pressure of 4 kN to obtain tablets.

[0206] The tablets were put into a coating machine "HC-FZ-LABO" (manufactured by Freund Sangyo Co., Ltd.) and coated with a coating solution prepared by dissolving 64.8 g of hypromellose (TC-5R, manufactured by Shin-Etsu Chemical Co., Ltd.), 8.1 g of polyethylene glycol 6000 (Macrogol 6000P, manufactured by NOF Corporation) and 8.1 g of titanium oxide (NA63, manufactured by Toho Titanium Co., Ltd.) in 729 g of pure water. The tablets were coated with 125 mg of mass, 3 mg of hypromellose, 0.375 mg of polyethylene glycol 6000 and 0.375 mg of titanium oxide per tablet to obtain coated tablets with a diameter of 7 mm and a mass of 128.75 mg.

[0207] [Example 6: Production of Tablet F]

[0208] To 96.5 g of the granulated material obtained in Reference Example 1, 42.8 g of crystalline cellulose (Ceolus PH-102, manufactured by Asahi Kasei Corporation) and 0.7 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and mixed thoroughly. The mixture was compressed using a rotary tablet press "VELAG" (manufactured by Kikusui Seisakusho Co., Ltd.) with a mass of 140 mg per tablet, 40 mg of pimetribuzin, 42.8 mg of crystalline cellulose (Ceolus PH-102), and a tableting pressure of 4.5 kN to obtain tablets.

[0209] The tablets were put into a coating machine "HC-FZ-LABO" (manufactured by Freund Sangyo Co., Ltd.) and coated with a coating solution prepared by dissolving 64.8 g of hypromellose (TC-5R, manufactured by Shin-Etsu Chemical Co., Ltd.), 8.1 g of polyethylene glycol 6000 (Macrogol 6000P, manufactured by NOF Corporation) and 8.1 g of titanium oxide (NA63, manufactured by Toho Titanium Co., Ltd.) in 729 g of pure water. The tablets were coated with 140 mg of mass, 3.36 mg of hypromellose, 0.42 mg of polyethylene glycol 6000 and 0.42 mg of titanium oxide per tablet to obtain coated tablets with a diameter of 7.5 mm and a mass of 144.2 mg.

[0210] [Example 7: Production of Tablet G]

[0211] To 96.5 g of the granulated material obtained in Reference Example 1, 102.5 g of crystalline cellulose (Ceolus PH-102, manufactured by Asahi Kasei Corporation) and 1 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and mixed thoroughly. The mixture was compressed using a rotary tablet press "VELAG" (manufactured by Kikusui Seisakusho Co., Ltd.) with a mass of 200 mg per tablet, 40 mg of pimetribuzin, 102.5 mg of crystalline cellulose (Ceolus PH-102), and a tableting pressure of 3.5 kN to obtain tablets.

[0212] The tablets were put into a coating machine "HC-FZ-LABO" (manufactured by Freund Sangyo Co., Ltd.), and coated with a coating solution obtained by dissolving 64.8 g of hypromellose (TC-5R, manufactured by Shin-Etsu Chemical Co., Ltd.), 8.1 g of polyethylene glycol 6000 (Macrogol 6000P, manufactured by NOF Corporation), and 8.1 g of titanium oxide (NA63, manufactured by Toho Titanium Co., Ltd.) in 729 g of pure water. The tablets were coated with 200 mg of mass, 4.8 mg of hypromellose, 0.6 mg of polyethylene glycol 6000, and 0.6 mg of titanium oxide per tablet to obtain coated tablets with a diameter of 8 mm and a mass of 206 mg.

[0213] [Comparative Example 3: Production of Tablet c]

[0214] To 96.5 g of the granulated material obtained in Reference Example 1, 301.5 g of crystalline cellulose (Ceolus PH-102, manufactured by Asahi Kasei Corporation) and 2 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and mixed thoroughly. The mixture was compressed using a rotary tablet press "VELAG" (manufactured by Kikusui Seisakusho Co., Ltd.) with a mass of 400 mg per tablet, 40 mg of pimidylpidem, 301.5 mg of crystalline cellulose (Ceolus PH-102), and a tableting pressure of 3.5 kN to obtain tablets.

[0215] The tablets were put into a coating machine "HC-FZ-LABO" (manufactured by Freund Sangyo Co., Ltd.), and coated with a coating solution obtained by dissolving 64.8 g of hypromellose (TC-5R, manufactured by Shin-Etsu Chemical Co., Ltd.), 8.1 g of polyethylene glycol 6000 (Macrogol 6000P, manufactured by NOF Corporation), and 8.1 g of titanium oxide (Titanium oxide NA63, manufactured by Toho Titanium Co., Ltd.) in 729 g of pure water. The tablets were coated with 400 mg of mass, 9.6 mg of hypromellose, 1.2 mg of polyethylene glycol 6000, and 1.2 mg of titanium oxide per tablet to obtain coated tablets with a diameter of 10 mm and a mass of 412 mg.

[0216] [Test Example 2: Determination of disintegration time]

[0217] The tablets prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were tested using a disintegration tester (NT-4H, NT-4H(P), manufactured by Toyama Sangyo Co., Ltd.) under the conditions of test liquid: water (37±2°C) and no disk, and the time from the tablet being put into the tester until the tablet was completely disintegrated was measured.

[0218] The results are shown in Tables 2 and 3.

[0219] [Table 2]

[0220]

[0221] [Table 3]

[0222]

[0223] The disintegration time of the crystalline cellulose with different physical properties was evaluated for the coated tablets obtained by coating the uncoated tablets in Table 2 (Examples 1 to 4 and Comparative Example 1). As a result, it was confirmed that the disintegration time of the coated tablets of Examples 1 and 2 was 3 minutes or less, the disintegration time of the coated tablets of Examples 3 and 4 was 5 minutes or less, and it was found that the disintegration time of the coated tablet of Comparative Example 1 required more than 15 minutes. The disintegration time of the coated tablets of Examples 1 and 2 was the most improved, but when the tableting pressure during tableting was confirmed, since the tableting pressure of Example 1 was about 4 kN and the tableting pressure of Example 2 was 5 kN, the amount of crystalline cellulose added was evaluated according to Example 1 from the viewpoint of moldability.

[0224] The disintegration time of the uncoated tablets in Table 3 (Examples 1, 5 to 7, Comparative Examples 2 and 3) was evaluated. As a result, it was found that in Examples 1, 5 to 7 and Comparative Example 2, the disintegration time became shorter according to the amount of crystalline cellulose added, but it was found that when the amount of crystalline cellulose added was large as in Comparative Example 3, the disintegration time was delayed. The disintegration time of the uncoated tablets and the disintegration time of the coated tablets have the same tendency. It can be considered that the amount of crystalline cellulose added is preferably 27.875 to 102.5 mg. The addition of a disintegrant is usually studied as the first choice for improving disintegrability, but surprisingly, a composition with excellent disintegrability can be obtained by adding crystalline cellulose and adjusting its amount without adding a disintegrant.

[0225] In addition, the sizes of the coated tablets of Examples 1, 5 to 7 and Comparative Examples 2 and 3 were compared. As a result, the coated tablets of Examples 1, 5 to 7 were all small-sized, 8 mm or less, while the coated tablet of Comparative Example 3 was 10 mm. Tablets are considered to be small and easy to take, especially when they are 7 to 8 mm, and have good medication compliance. The coated tablets of Examples 1, 5 to 7 are 7 to 8 mm, and are expected to be tablets with good medication compliance.

[0226] Furthermore, no tableting problems such as sticking were observed in the tablets of Examples of the present invention.

[0227] [Test Example 3: Measurement of bulk density and major diameter / minor diameter ratio]

[0228] For crystalline cellulose (Ceolus PH-102, PH-302, KG-802, UF-711, KG-1000, manufactured by Asahi Kasei Corporation), the bulk density was determined using a powder tester (PT-R, manufactured by Hosokawa Micron Co., Ltd.) according to the bulk density and tap density measurement method specified in the Japanese Pharmacopoeia. In addition, the major and minor diameters of 50 particles were measured using an electron microscope (VHX-D500, manufactured by Keyence Co., Ltd.) to determine the major-to-minor ratio.

[0229] The results are expressed in Figure 1 .

[0230] [Example 8: Production of Tablet H]

[0231] 3000 g of pimetribizol (manufactured by Alps Pharmaceutical Co., Ltd.), 2887.5 g of lactose hydrate (Lactochem fine powder, manufactured by DMV Fonterra Excipients GmbH & Co. KG), and 1125 g of corn starch (Nisshoku Cornstarch W, manufactured by Nippon Food Chemical Co., Ltd.) were put into a fluidized bed granulator "FLC-3N-5" (manufactured by Freund Sangyo Co., Ltd.), and 2250 g of a combined solution obtained by dissolving 400 g of hydroxypropyl cellulose (HPC SSL, manufactured by Nippon Soda Co., Ltd.) in 3600 g of pure water was used for fluidized bed granulation. A granulator "QC-U10" (manufactured by Powrex Co., Ltd.) was used, and the impeller speed was 400 min. -1 The granules are sized to obtain granules.

[0232] To 144.75 g of the obtained granules, 79.125 g of crystalline cellulose (Ceolus PH-102, manufactured by Asahi Kasei Corporation) and 1.125 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added and thoroughly mixed, and tablets were pressed using a rotary tablet press "VELAG" (manufactured by Kikusui Seisakusho Co., Ltd.) with a mass of 150 mg per tablet, 40 mg of pimidel, 52.75 mg of crystalline cellulose (Ceolus PH-102), and a hardness of 70N.

[0233] The tablets were put into a coating machine "HC-FZ-LABO" (manufactured by Freund Sangyo Co., Ltd.), and coated with a coating solution obtained by dissolving 40 g of hypromellose (TC-5R, manufactured by Shin-Etsu Chemical Co., Ltd.), 5 g of polyethylene glycol 6000 (Macrogol 6000P, manufactured by NOF Corporation), and 5 g of titanium oxide (NA63, manufactured by Toho Titanium Co., Ltd.) in 450 g of pure water. The tablets were coated with 154.5 mg of mass, 3.6 mg of hypromellose, 0.45 mg of polyethylene glycol 6000, and 0.45 mg of titanium oxide per tablet to obtain coated tablets with a diameter of 7 mm and a mass of 154.5 mg.

[0234] [Comparative Example 4: Production of Tablet d]

[0235] 3000 g of pimetribizol (manufactured by Alps Pharmaceutical Co., Ltd.), 2887.5 g of lactose hydrate (Lactochem fine powder, manufactured by DMV Fonterra Excipients GmbH & Co. KG), and 1125 g of corn starch (Cornstarch, manufactured by Nippon Food Chemical Co., Ltd.) were put into a fluidized bed granulator "FLC-3N-5" (manufactured by Freund Sangyo Co., Ltd.), and 2250 g of a combined solution obtained by dissolving 450 g of hydroxypropyl cellulose (HPC SSL, manufactured by Nippon Soda Co., Ltd.) in 4050 g of pure water was used for fluidized bed granulation. A granulator "QC-U10" (manufactured by Powrex Co., Ltd.) was used, and the impeller speed was 400 min. -1 Granulation is performed to obtain granules.

[0236] 180.16 g of croscarmellose sodium (Ac-Di-Sol SD-711, manufactured by FMC Health and Nutrition) and 30.03 g of magnesium stearate (specially made, plant-based, manufactured by Taihei Chemical Industry Co., Ltd.) were added to 5795.15 g of the granulated material and mixed thoroughly. The mixture was compressed using a rotary tablet press "AQUARIUS C-H" (manufactured by Kikusui Seisakusho Co., Ltd.) with a mass of 100 mg per tablet, 40 mg of pimetribuzin, 3 mg of croscarmellose sodium, and a hardness of 60 N.

[0237] The tablets were put into a coating machine "PRC-10GTX" (manufactured by Powrex Co., Ltd.) and coated with a coating solution obtained by dissolving 360 g of hypromellose (TC-5R, manufactured by Shin-Etsu Chemical Co., Ltd.), 45 g of polyethylene glycol 6000 (Macrogol 6000P, manufactured by NOF Corporation), and 45 g of titanium oxide (NA63, manufactured by Toho Titanium Co., Ltd.) in 4050 g of pure water. The tablets were coated with 103 mg of mass, 2.4 mg of hypromellose, 0.3 mg of polyethylene glycol 6000, and 0.3 mg of titanium oxide per tablet to obtain coated tablets with a diameter of 6 mm and a mass of 103 mg.

[0238] Table 4 shows the compositions of the coated tablets of Example 8 and Comparative Example 4.

[0239] [Table 4]

[0240]

[0241] [Test Example 4: Dog Absorption Test]

[0242] For the coated tablets prepared by Example 8 and Comparative Example 4, 2 tablets were administered to each individual with 50 mL of water (80 mg / body) for 6 males, about 9-11 kg, 39-44 months old, fasting, 30 minutes before administration, atropine sulfate intravenous injection 20 μg / 0.04 mL / kg was intravenously administered, and pentagastrin intramuscular injection 10 μg / 0.1 mL / kg was intramuscularly administered. Then, the same amount of pentagastrin intramuscular injection was administered twice at intervals of 45 minutes. Blood was collected from the skin vein of the forearm using a syringe and needle (21G) treated with heparin at 0.25, 0.5, 1, 2, 4, 8 and 24 hours after administration. The collected blood was centrifuged (12000rpm, 5°C, 3 minutes), and 50μL of the obtained plasma was collected in a polypropylene microtube, 50μL of acetonitrile and 100μL of the internal standard solution were added, and mixed with a vortex mixer. After centrifugation (20400g, 5°C, 1 minute), 100μL of the supernatant was collected in a polypropylene automatic sampling tube, 200μL of water was added, and mixed with a vortex mixer. The obtained sample was quantified using a high performance liquid chromatography / mass spectrometer (ABSciex Co., Ltd.), and the Tmax value, Cmax value, and AUC were calculated.

[0243] <Liquid chromatography measurement conditions>

[0244] Equipment: High performance liquid chromatography / mass spectrometer (AB Sciex Co., Ltd.)

[0245] Chromatographic column: Imtakt Unison uk-c18 (2.0mm id×50mm, 3μm)

[0246] Column temperature: 40°C

[0247] Mobile phase A: 10mmol / L ammonium formate solution

[0248] Mobile phase B: acetonitrile

[0249] Liquid delivery of mobile phase: Set the mixing ratio of mobile phase A and mobile phase B to 67:33 or 65:35, and deliver liquid from the pump. Flow rate: 0.3mL / min

[0250] MS / MS measurement conditions

[0251] Ionization source: electrospray ionization (ESI) - positive

[0252] Scan mode: Multiple reaction monitoring (MRM)

[0253] For the coated tablets of Table 4 (Example 8 and Comparative Example 4), an absorption test was conducted using beagle dogs (6 males, about 9 to 11 kg, 39 to 44 months old). The results showed that the relative BA of Example 8 was 146% relative to that of Comparative Example 4, and that the absorbability could be improved by using crystalline cellulose instead of a disintegrant ( Figure 2 , Table 5).

[0254] [Table 5]

[0255]

Claims

1. A pharmaceutical composition, characterized in that: The invention comprises a granulated material and crystalline cellulose, wherein the granulated material contains 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof, The pharmaceutical composition has a disintegration time of 360 seconds or less in the state of a coated tablet.

2. A pharmaceutical composition, characterized in that: The pharmaceutical composition is obtained by mixing a granulated material and 20.0 to 55.0% by mass of crystalline cellulose, wherein the granulated material contains 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propane-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof, The crystalline cellulose has an L / D ratio of 1.00 to 4.00 and / or a bulk density of 0.20 to 0.50 g / cm before mixing. 3 .

3. A pharmaceutical composition, characterized in that Include: A granulated material containing 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof; and 20.0 to 55.0% by mass of crystalline cellulose, wherein the crystalline cellulose is selected from Ceolus PH-102, PH-302, KG-802 and UF-711.

4. The pharmaceutical composition according to claim 2 or 3, characterized in that: The content of the crystalline cellulose is 30.0 to 55.0% by mass.

5. The pharmaceutical composition according to any one of claims 2 to 4, characterized in that: The uncoated tablet has a disintegration time of 180 seconds or less, or the coated tablet has a disintegration time of 360 seconds or less.

6. The pharmaceutical composition according to any one of claims 1 to 5, characterized in that: The present invention contains 18.0 to 40.0% by mass of 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propan-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof.

7. The pharmaceutical composition according to any one of claims 1 to 6, characterized in that: The granulated material is a granulated material obtained by a wet granulation method.

8. The pharmaceutical composition according to any one of claims 1 to 7, characterized in that: The average particle size d50 of the granulated material is 50 to 400 μm.

9. The pharmaceutical composition according to any one of claims 1 to 8, characterized in that: It is a solid preparation.

10. The pharmaceutical composition according to claim 9, characterized in that: It is a tablet.

11. The pharmaceutical composition according to claim 10, characterized in that: The diameter is 6.5~9.5mm.

12. A coating composition, characterized in that: The pharmaceutical composition according to any one of claims 1 to 11 is coated.

13. A method for producing a pharmaceutical composition, characterized in that: include: A step of granulating a powder using a binding liquid, wherein the powder comprises 3-ethyl-4-{4-[4-(1-methyl-1H-pyrazol-4-yl)-1H-imidazol-1-yl]-3-(propane-2-yl)-1H-pyrazolo[3,4-b]pyridin-1-yl}benzamide or a pharmaceutically acceptable salt thereof; and A step of mixing the granulated material obtained in the above step with crystalline cellulose so that the content of the crystalline cellulose in the pharmaceutical composition becomes 20.0 to 55.0% by mass, wherein the L / D ratio of the crystalline cellulose is 1.00 to 4.00 and / or the bulk density is 0.20 to 0.50 g / cm 3 .

14. The method for producing the pharmaceutical composition according to claim 13, wherein: The granulation method is a fluidized bed granulation method.

15. A pharmaceutical composition obtained by the method of claim 13 or 14.

Citation Information

Patent Citations

  • Azabicyclo compound and salt thereof

    WO2011004610A1

  • Combination cancer therapy using azabicyclo compound

    WO2015046498A1

  • Crystals of azabicyclic compound

    WO2016181990A1

  • Chemotherapy for cancer using azabicyclo compound

    WO2019004417A1

  • Prophylactic and / or therapeutic agent for diseases involving IDO expression

    WO2019054465A1

Cited By

  • Application of pimitinib in preparation of medicine for treating tumors

    CN121197156A